2018
DOI: 10.1101/372599
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phase-dependent suppression of beta oscillations in Parkinson’s disease patients

Abstract: Synchronized oscillations within and between brain areas facilitate normal processing, but are often amplified in disease. A prominent example is the abnormally sustained beta-frequency (~20Hz) oscillations recorded from the cortex and subthalamic nucleus of Parkinson's Disease patients. Computational modelling suggests that the amplitude of such oscillations could be modulated by applying stimulation at a specific phase. Such a strategy would allow selective targeting of the oscillation, with relatively littl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 82 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…This activity became significant only ON medication (IntraMed analysis). Since synchrony limits information transfer, 4850 local oscillations are a potential mechanism to prevent excessive communication with the cortex. Another possibility is that a loss of cortical afferents causes, local basal ganglia oscillations to become more pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…This activity became significant only ON medication (IntraMed analysis). Since synchrony limits information transfer, 4850 local oscillations are a potential mechanism to prevent excessive communication with the cortex. Another possibility is that a loss of cortical afferents causes, local basal ganglia oscillations to become more pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive synchronization of beta oscillations attributed to dopamine deficiency in PD has for example been observed across cortical areas and the BG (Williams et al, 2002;Litvak et al, 2010;Hirschmann et al, 2011;Koren et al, 2022), and disrupting beta synchronization in cortical (Doyle Gaynor et al, 2008) and BG nodes, including striatum (Costa et al, 2006;McCarthy et al, 2011), pallidum , subthalamic nucleus (de Solages et al, 2010;Darcy et al, 2022) and thalamus (Van Der Werf et al, 2006), results in improvements of bradykinesia, rigidity, and freezing. Precisely timing transcranial magnetic stimulation (TMS) to the opposing phase of the optimal window of ongoing beta oscillations in cortical regions may likewise present an effective non-invasive intervention for personalized modulation (Cassidy et al, 2002;Sharott et al, 2018), similar as has been demonstrated for phase-specific STN stimulation (Holt et al, 2019).…”
Section: Effect Of Beta Oscillatory Phase On Inhibitory Motor Controlmentioning
confidence: 94%